Chemical and biological oxidation of NOM surrogates and effect on HAA formation - Bond, Tom; Goslan, Emma H.; Jefferson, Bruce; Roddick, Felicity A.; Fan, Linhua; Parsons, Simon A. (Elsevier, 2009)
Formation of disinfection by-products (DBPs) can be controlled by removal of disinfection by-product precursors before disinfection. Variable success has been reported, depending on the treatment used and water tested. Chemical and biological oxidations are candidate technologies to control DBP formation. Given the uncertainty over the identity of DBP precursors, the use of surrogates of natural organic matter (NOM) allows fundamental probing of the links between compound character, removal and DBP formation. Nine compounds were chosen to represent NOM and their removal by two advanced oxidation processes (AOPs), UV-C irradiation and biological treatment compared while haloacetic acid (HAA) formation before and after treatment was measured. Although AOPs were able to fully remove all compounds, incomplete mineralisation led to increased HAA levels, dramatically in the case of two amino acids. Biological treatment was effective in removing amino acids but also moderately increased the HAA formation potential (HAAFP) of hydrophilic compounds. These findings indicate waters with high amino acid concentrations will be susceptible to raised HAA levels following AOP treatment and careful process selection for HAA control is required in such cases.
Keywords: HAAs; AOPs; Biotreatment; NOM; Treatability